Mastering CSS Grid : an extensive practical guide to creating beautiful layouts with CSS Grid - Thormeier, Pascal (Packt Publishing, 2023)
Explore the full spectrum of CSS Grid concepts and efficiently leverage its specifications with a project that incorporates both basic and advanced aspects Purchase of the print or Kindle book includes a free PDF eBook Key Features Explore the differences between grid boxes and block containers to enhance your web design knowledge Create block-level grids, inline grids, and nested grids to create responsive layouts Adopt best practices for attaching elements to your layout by using explicitly defined grid lines or grid areas Book Description CSS Grid has revolutionized web design by filling a long-existing gap in creating real, dynamic grids on the web. This book will help you grasp these CSS Grid concepts in a step-by-step way, empowering you with the knowledge and skills needed to design beautiful and responsive grid-based layouts for your web projects. This book provides a comprehensive coverage of CSS Grid by taking you through both fundamental and advanced concepts with practical exercises. You'll learn how to create responsive layouts and discover best practices for incorporating grids into any design. As you advance, you'll explore the dynamic interplay between CSS Grid and flexbox, culminating in the development of a usable responsive web project as a reference for further improvement. You'll also see how frameworks utilize CSS Grid to construct reusable components and learn to rebuild and polyfill CSS Grid for browsers that don't fully support it yet. The concluding chapters include a quick reference and cheat sheet, making this book an indispensable resource for frontend developers of all skill levels. By the end of this book, you'll have thoroughly explored all aspects of CSS Grid and gained expert-level proficiency, enabling you to craft beautiful and functional layouts for web projects of any size. What you will learn Enhance your CSS Grid skills by mastering both its fundamental and advanced concepts Combine flexbox and CSS Grid seamlessly to produce stunning and responsive page layouts Discover the potential of complex grid layouts to improve your next project Examine how frameworks utilize CSS Grid to create reusable components Leverage the benefits of grid-based layouts to create visually appealing websites Create custom polyfills and learn when to use grid layouts Build dynamic and user-friendly web projects using CSS Grid's responsive design capabilities Who this book is for This book is for web developers and designers who want to learn CSS Grid and improve their layout design skills. This book will also be a valuable resource for CSS developers seeking to advance their skills to the most proficient level. Additionally, this book will serve as an excellent guide for those who wish to expand their toolset to include flexbox and grids.